Prevalence of Helminthic Infections in the Gastrointestinal Tract of Cattle in Mazandaran Province (Northern Iran) - Nasrollah Vahedi Nouri; Reza Rahmatian; Alireza Salehi (Journal of Parasitology Research)
Ruminant parasites are found in all parts of the world, including the tropical and subtropical regions. Mazandaran province (northern Iran) is one of the areas prone to the activity of gastrointestinal parasites in ruminants. This study was performed in 2020, in order to identify common parasites of cattle gastrointestinal tract, the percentage of the infection, the effect of seasons, and livestock on the amount of infection and determine the severity of infection. In this study, seven genera of gastrointestinal parasites including Strongyloides, Haemonchus, Ostertagia, Cooperia, Trichostrongylus, Oesophagostomum, and Chabertia were identified among 240 cattle. Overall, 34.58% of cows were infected with different kinds of parasites. Based on the average percentage of livestock infected with gastrointestinal parasites across different seasons, winter had the lowest percentage (18.33%) compared to other seasons, which has a statistically significant difference (P<0.05). Also, we observe that the female cattle’s infection rate, in comparison with males, had no significant difference (P<0.05). Moreover, 67.17% of the cattle had a moderate level of infection. Despite the fact that farmers use antiparasitic drugs, helminthic infections in cattle are still high. In conclusion, the lack of proper implementation of helminthic infection control programs as well as antiparasitic drug resistance in this area can be a key element for the high prevalence of livestock helminthic infection in these areas.